SWI/SNF chromatin remodelling complex contributes to clearance of cytoplasmic protein aggregates and regulates unfolded protein response in Saccharomyces cerevisiae. (5th January 2020) - Sahu, Rakesh Kumar; Saha, Nitu; Das, Laxmidhar; Sahu, Pushpendra Kumar; Sariki, Santhosh Kumar; Tomar, Raghuvir Singh
Abstract : Chromatin remodelling complexes are multi‐subunit assemblies, each containing a catalytic ATPase and translocase that is capable of mobilizing nucleosomes to alter the chromatin structure. SWI/SNF remodelling complexes with higher DNA translocation efficiency evict histones or slide the nucleosomes away from each other making DNA accessible for transcription and repair machinery. Chromatin remodelling at the promoter of stress‐responsive genes by SWI/SNF becomes necessary during the heat and proteotoxic stress. While the involvement of SWI/SNF in transcription of stress‐responsive genes has been studied extensively, the regulation of proteostasis by SWI/SNF is not well understood. This study demonstrates critical functions of SWI/SNF in response to cadmium‐induced proteotoxic stress. Deletion of either ATPase–translocase subunit of SWI/SNF complex (Swi2/Snf2) or a regulatory subunit Swi3 abrogates the clearance of cadmium‐induced protein aggregates. Our results suggest that Snf2 and Swi3 regulate the protein folding in endoplasmic reticulum (ER) that reduces the chances of forming unfolded protein aggregates under the proteotoxic stress of cadmium. The Ire1‐mediated unfolded protein response (UPR) maintains ER homeostasis by upregulating the expression of chaperones and ER‐associated degradation (ERAD) components. We found that Snf2 maintains normal oxidative environment essential for Ire1 activity. Deletion of SNF2 reduced the Ire1 activity and UPR, indicating involvement of Snf2 in Ire1‐mediated ER proteostasis. Together, these findings suggest that SWI/SNF complex regulates ER homeostasis and protein folding crucial for tolerating proteotoxic stress. Abstract : Regulation of endoplasmic reticulum (ER) homeostasis is critical to tolerate proteotoxic agents like cadmium. Ire1‐mediated unfolded protein response (UPR) maintains ER homeostasis under stress. Snf2, the catalytic component of SWI/SNF chromatin remodelling complex, is involved in regulation of Ire1 activity and UPR induction. Snf2 indirectly regulates Ire1 activity by maintaining cellular redox balance. Cadmium targets newly synthesized peptides to form cytoplasmic aggregates. We show that Snf2 and Swi3 prevent formation of protein aggregates.